Expander processing conditions affect nutrient digestibility in finishing pigs fed corn-, sorghum-, wheat-, and wheat midds-based diets - S L Traylor; Robert H Hines; D J Lee; S L Johnston; P Sorrell; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1998)
Expander processing of corn-, sorghum-, wheat-, and wheat midds-based diets improved nutrient digestibility in growing pigs and, thus, the apparent digestible energy concentration in the diets. This new feed manufacturing technology was especially beneficial to the feedstuff with the highest fiber content (i.e., wheat midds).; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Expander; Corn; Sorghum; Wheat midds